The narrow corridor : states, societies, and the fate of liberty - Acemoglu, Daron; Robinson, James A. (Penguin Press, 2019)
There is a Western myth that political liberty is a durable construct, arrived at by a process of "enlightenment." This static view is a fantasy, the authors argue. In reality, the corridor to liberty is narrow and stays open only via a fundamental and incessant struggle between state and society: The authors look to the American Civil Rights Movement, Europe$1 (Bs early and recent history, the Zapotec civilization circa 500 BCE, and Lagos$1 (Bs efforts to uproot corruption and institute government accountability to illustrate what it takes to get and stay in the corridor. But they also examine Chinese imperial history, colonialism in the Pacific, India$1 (Bs caste system, Saudi Arabia$1 (Bs suffocating cage of norms, and the (3z(BPaper Leviathan(3y (Bof many Latin American and African nations to show how countries can drift away from it, and explain the feedback loops that make liberty harder to achieve. s
Keywords: Liberty; Power (Social sciences) -- Political aspects; Direct democracy; Decentralization in government; Violence -- Political aspects